Avaliacao preliminar da utilizacao do residuo industrial de man dioca (manihot esculenta granz) como excipiente em comprimidos: Caracteristicas fisicas e de compressao - Castro, Ana Doris de [UNESP]; Hamilton Ferreira Bueno, J. [UNESP]; Chin, Chung Man [UNESP] (My University, 1998)
The applicability of a residue of manioc (Manihot esculenta Granz) from industrial processing as a direct compression excipient was investigated in comparison with microcrystalline cellulose (Avicel® PH 101). Physical characteristics of the powders like bulk and tap densities, particle size, flow properties (flow rate, index of compressibility and angle of repose) and agglutination were evaluated. The residue had poor performance as excipient for direct compression. However, it showed better disintegration properties than Avicel. The possibility of its use as disintegrant agent will be confirmed on future studies.
Preliminar evaluation of the applicability of a residue of manioc (Manihot esculenta Granz) as a direct excipient in tablets: Physical and compression characteristics
Keywords: Binders and adhesives; Disintegrant; Excipients for tablets; Manioc bran; Microcrystalline cellulose; disintegrating agent; excipient; microcrystalline cellulose; cassava; controlled study; density; flow rate; particle size; physical chemistry; tablet compression; tablet disintegration